Rancangan program alternatif metrik pada Pusat Pengelolaan Pengetahuan Universitas Padjadjaran - Ilyas Lanang Sinatria; Edwin Rizal; Kusnandar Kusnandar (Faculty of Communication, Padjadjaran University, 2023)
Padjadjaran University Knowledge Management Center has rebuilt its website by adding the GLAM Repository element. The website plans to install alternative metric tools: PlumX which is found in a subscription package repository called Digital Commons. This research aims to create a program design based on the four substances of information system management: technology, databases, procedures, and human resources. This study uses a qualitative approach with method action research. The data collection process is carried out using interviews, observation, literature studies, documentation, and focus group discussions. Data are gathered from librarians and staff through interviews and FGDs. Data analysis techniques conducted by researchers included: data reduction, data presentation, and data conclusion. Results researched shows that in the field of technology and databases, the website was rebuilt through the addition of GLAM and repository elements. Knowledge Management Center unify databases between faculty libraries. Alternative metric procedures has been successfully submitted to Universitas Padjadjaran. The librarians need to learn about alternative metrics. The outputs of alternative metric implementation program designs are proposals, draft terms of reference, and Digital Common and Plumx learning materials. The conclusion of the research is that the design of alternative metric programs requires technological support, databases, updating of computer units, and staff training in managing alternative metrics.